Creatine kinase equilibrium and lactate content compared with muscle pH in tissue samples obtained after isometric exercise - Kent Sahlin; Roger C. Harris; E. Hultman (1975)
Muscle biopsies taken from the musculus quadriceps femoris of man were analysed for pH, ATP, ADP, AMP, creatine phosphate, creatine, lactate and pyruvate. Biopsies were taken at rest, after circulatory occlusion and after isometric contraction. Muscle pH decreased from 7.09 at rest to 6.56 after isometric exercise to fatigue. Decrease in muscle pH was linearly related to accumulation of lactate plus pyruvate. An increase of 22mumol of lactate plus pyruvate per g of muscle resulted in a fall of 0.5pH unit. The apparent equilibrium constant of the creatine kinase reaction (apparent K(CK)) increased after isometric contraction and a linear relationship between log(apparent K(CK)) and muscle pH was obtained. The low content of creatine phosphate in muscle after contraction as analysed from needle-biopsy samples is believed to be a consequence of an altered equilibrium state of the creatine kinase reaction. This in turn is attributed mainly to a change in intracellular pH.